Dynamics of Legal Pluralism and an emerging legal Hybridism : the Duality of cooperation and 0contestation between customary, Religious and state dispute resolutions among the Siltie people of Southern Ethiopia - Kairedin Tezera (Addis Ababa:. : Eclipse Printing press, 2018)
This book is about dynamics of identity formation and legal pluralism among the Siltie people in an ethnic federal state of Ethiopia. Ethiopia has not published any Ethiopian Ethnicities in the Ethiopia. Since 1991, the country has been embarked on a unique political experiment known as "ethnic federalism." The 1995 Constitution of the Federal Democratic Republic of Ethiopia grants specific rights to ethnic groups, which ultimately entails the recognition of ethnic-juridical orders. By examining the versatile relationship between the Ethiopian state and the Siltie people (an ethnic group who resides in Southern Nations 'Nationalities and People' This book provides an anthropological understanding of the legal dynamics of state-society relations, focusing on Silties people in southern Ethiopia. Previous Socio-Legal and Anthropological Studies mostly focusing on the binary nature of legal systems. The literature categorizes legal systems into simple, primitive, formal or informal, labeling the informal legal regimes as (not) norm imposing and having little legal natures (less legal status) than what they consider to be modern and more institutionalized legal systems (Malinowski, 1926, Radcliff-Brown, 1942). Ethiopia has focused on comparing the state system with the customary courts, and usually tend to be descriptive (eg, Gebre et al., 2013, Alula and Getachew, 2008). Prior studies have also excluded the dynamics witnessing in the area of ??legal pluralism in the country. In addition, they failed to address the complexity of plural legal settings in the context. In an attempt to fill these gaps, the following four inter-related research questions are addressed: What are the legal systems the Siltie employ? How do legal systems interact in the area? Why and how do you disputants prefer one form of conflict resolution to the other in a pluralistic legal setting? By the dualism of cooperation and competition. The interactions of legal systems and display of contradictory perspectives and cross into territories claimed by the other. This ambivalent relationship hints at the porosity of the different systems. The research data are mainly used in the employment of a legal anthropological approach, with the extended case method and ethnography as the main research techniques employed.
Keywords: Sociology and anthropology